Assessment of Azithromycin in Pharmaceutical Formulation by Fourier-transform Infrared (FT-IR) Transmission Spectroscopy - Muhammad Ali Mallah; S.T.H. Sherazi; Sarfaraz A. Mahesar; Abdul Rauf (Pakistan Journal of Analytical & Environmental Chemistry, 2011)
A simple, rapid and economical method for azithromycin quantification in solid tablet and capsule formulations has been developed by applying Fourier-transform Infrared (FT-IR) transmission spectroscopy for regular quality monitoring. The newly developed method avoids the sample preparation, except grinding for pellet formation and does not involve consumption of any solvent as it absolutely eliminates the need of extraction. KBr pellets were employed for the appraisal of azithromycin while acquiring spectra of standards as well as samples on FT-IR. By selecting the FT-IR carbonyl band (C=O) in the region 1,744–1,709 cm−1 the calibration model was developed based on simple Beer’s law. The excellent regression coefficient (R2) 0.999 was accomplished for calibration set having standard error of calibration equal to 0.01 mg. The current work exposes that transmission FT-IR spectroscopy can definitely be applied to determine the exact amount of azithromycin to control the processing and quality of solid formulations with reduced cost and short analysis time.